The small incisions combined with interrupted buried suture blepharoplasty: flexible-rigid fixation - Cao, Jingjing; Yan, Lingling (Frontiers in Medicine, 2024)
Background: The traditional full incision blepharoplasty is the most commonly used in Asia. However, it has significant drawbacks like long recovery period, excessive surgical marks etc. We offer a new suture idea and combine it with interrupted suture buried blepharoplasty to improve these disadvantages. Methods:In our procedure, the orbital septum is opened and separating the levator aponeurosis-the retro-orbital septum complex under this 3-5 millimeters small incision, a flexible-rigid fixation would be made: suture fixation was made to the tarsus-the complex-lower lip orbicularis oculi muscle. We interrupted bury the sutures in the uncut skin between the two small incisions. Results:This paper included 333 patients divided into small incision groups using flexible-rigid fixation (n=244, 73.3%) and full incision groups using rigid fixation (n=89, 26.7%). Both at 6-month and at 5-year postoperative follow-up, the satisfaction of small incision group was statistically higher than the full incision group. The overall postoperative complication rate was statistically significantly less in the small incision. The permanence was not statistically different. For Assignment of Postoperative Effort Score (PES) results, at 6 months postoperatively, the mean score was 8.29 ± 1.32 in the small incision group, 7.86±1.54 in the full incision group. At 5 years postoperatively, the mean score was 7.48 ± 1.45 in the small incision group, 7.51±1.73 in the full incision group. None were statistically different. Conclusion: The small incisions group achieves a higher level of patient satisfaction and more mild trauma in the surgical area, has a low complication rate, and a decent degree of durability.